Strong Nucleating Effect of Si-Containing Tri-Block Oligomers on Poly(Ethylene Terephthalate) - Quankai Sun; Yao Wang; Miaorong Zhang; Linjun Huang; Pengwei Zhang; Kang Li; Wei Wang; Jianguo Tang (Molecules)
The development of a silane coupling agent with an aminopropyl structure as a nucleating agent for poly(ethylene terephthalate) (PET) is reported in this study. The tri–block oligomers nucleating agent was formed by 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane/oxalic acid/low molecular weight PET (LPOBD). It was subsequently cross-linked with tetraethyl orthosilicate to form LPOBD-T. Composites of LPOBD/PET and LPOBD-T/PET were prepared by melt blending, and their thermal and crystallization behaviors were analyzed using XRD, DSC, TG, and POM. The results indicated that not only did the triblock polymer nucleating agent LPOBD exhibit a strong nucleation effect, but the crosslinked LPOBD-T also demonstrated superior crystallization performance. Specifically, the crystallinity of the 1 wt% LPOBD-T/PET composite increased by 3.3%, the crystallization temperature rose by 21.1 °C, and the t1/2 was reduced by 53 s. Moreover, the crystalline morphology was more uniform. These findings indicate that the tri-block oligomers synthesized from a silane coupling agent serve as effective nucleating agents for PET.